IDENTIFIKASI PENERAPAN K3 PADA GEDUNG PEMERINTAH (STUDY KASUS GEDUNG KEJATI KALIMANTAN BARAT) - Sarlinton, Pristanto Nugroho; Pratiwi, Riyanny; Syahruddin, - (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
This study aims to determine the risk of any K3 that may occur in building construction work and analyze the factors causing the risk. The risk analysis is to know the risk of K3 most common in building construction work based on the result of questionnaires distributed to respondents who work on building construction work. The amount of risk of K3 will be analyzed by using Fine method. Furthermore, risk evaluation will be performed and the last is to provide risk control. In this study, the highest risk is the risk of falling from the height on the work formwork installation of 248.10. From the value of risk, the risk of falling from a height including into the level of risk Priority 1 that needs to be done immediately. Handling is done by providing risk control in the form of K3 field implementation include the use of APD, warning signs and standardization of safety when working at an altitude.Â Keywords:Â Risk management, occupational safety and health (K3), work accident